Theory and Praxis of Social Ministry in the Mission of the Redeemed Christian Church of God - Adebayo, Kehinde Francis (Vrije Universiteit Amsterdam, 2023)
This study of the theology implicit in the social practice of the RCCG explores the struggle for a holistic mission approach by highlighting the failure of the Lausanne congresses to provide a missiology that gives equal place to social ministry and gospel proclamation as components of mission. It also showed that the Latin American contribution of Integral mission cannot entirely respond to the African question because of the difference in worldviews. It was argued that Latin Americans interpreted their socioeconomic predicament from a sociohistorical standpoint, whereas Africans tend to interpret theirs from a standpoint that includes spiritual forces. This particular African approach positions African Pentecostalism for implicit and explicit theological investigation. In this study, the Pentecostal family is represented by the RCCG. The study applied a hybrid of methods to demonstrate that Pentecostalism in Africa and elsewhere are not oblivious to social ministry as a component of mission. It was also affirmed that the observation of Pentecostalism’s alleged lack of social vision is based on the paucity – until recently, that is – of Pentecostal theological literature on the nature of social ministry in the context of the church’s mission. It was noted that African Pentecostals demonstrate contextual sensitivity by addressing African problems and phenomena, by holistically drawing on the African religious worldview. In the end, the study sheds light on the rather scanty picture of African Pentecostal mission, especially its social component.
Free
Keywords: missiologie; afrika; pinksterkerk; theologie; de redeemed christian church of god.; pentecostalism. africa. mission. missiology. social ministry. nigeria. worldview. yoruba.